ADHD and Motor Perception Dysfunction Comorbidity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The epidemiology, co-morbidity and overlap of attention deficit hyperactivity disorder (ADHD) and deficits in attention, motor control and perception (DAMP), as defined in Scandinavia, were assessed in a total population of 589 6-year-old children screened for neurodevelopmental and neuropsychiatric disorders at the Skovde Central Hospital, and the University of Goteborg, Sweden.